Artificial iris implantation in a male with post-traumatic aniridia – case report - Wągrowska, Maria; Wilczyński, Michał; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2016)
Artificial iris implantation in a 38-year-old patient with post-traumatic aniridia is reported. The patient was assaulted in May 2013 and suffered a blunt trauma to his left eye. Directly after the assault, he was treated at the local hospital, where the upper eyelid wound and the lacerations of bulbar conjunctiva were sutured. One month later, he underwent a combined procedure of cataract extraction and anterior vitrectomy without the implantation of an intraocular lens. Next, he was hospitalised in our department, where apart from medical treatment of secondary, post-traumatic glaucoma, he was diagnosed with aphakia and almost complete aniridia. Afterhis intraocular pressure normalized, he had an artificial iris prosthesis and intraocular lens implanted. The surgery was uneventful. The patient was very satisfied with the surgery. He reported a significant symptomatic improvement and resolution of photophobia and glare. The aesthetic result was very good. The customized artificial iris may be an effective treatment option in traumatic aniridia. It may improve the quality of life, as it reduces the unwanted optical phenomena occurring in aniridia. Furthermore, it offers excellent aesthetic result.